Analyzing government decision making in the South African biofuels industry: a game theoretic approach. Issue 3 (May 2011) - Funke, T; Klein, P
The production of biofuels in many countries is largely driven by the government strategy and incentives that are in place. In South Africa the first round of the development of such a draft strategy took place in 2005, with the official stance on biofuels finalized in December 2007. During the policy-development process, various governmental departments had strategic goals and targets that they were all required to achieve. The achievement of these strategic targets and goals is risky and the various departments that have some form of involvement in the biofuels industry need to decide on how much risk they are willing to take. This article sketches the game that the various governmental departments played as well as the risks that they were faced with when writing the Industrial Biofuels Strategy. In establishing a Nash equilibrium and when comparing this with the current state of affairs in the industry, an investigation is launched as to what has caused the governmental department to divert so strongly from its position. A variable, z, is defined and included in the model in order to explain the current state of affairs. This variable is analyzed further in order to bring some form of structure to the debate on the government''s stance on this issue.